Employee Engagement in SMEs: A Systematic Review of the Literature on Factors and Their Impact - Sangapan, Lukman Hakim; Manurung, Adler Haymans; Manurung, Catarina; Manurung, Amran; Manurung, Gerson (Dinasti Research, 2021)
This study aims to identify the factors influencing employee engagement in Small and Medium Enterprises (SMEs) and evaluate their impact on organizational performance. A systematic literature review approach was employed, analyzing 20 relevant scientific articles selected through a predefined inclusion and exclusion criteria. Thematic analysis was used to identify recurring patterns and key themes across the literature. The findings reveal that leadership style, internal communication, organizational culture, reward systems, and employee well-being are the dominant factors positively influencing employee engagement. These elements have been shown to enhance job satisfaction, loyalty, productivity, and employee retention within SMEs. This research contributes conceptually by developing a systematic framework that can serve as a foundation for building employee engagement models tailored to the SME context. Furthermore, it offers practical implications for SME management in designing more participatory and empowerment-oriented human resource strategies. The study acknowledges its limitation in relying solely on secondary data sources and recommends further empirical field studies to validate the findings across various industry sectors.